A preliminary study of intestinal microsporidiosis among Orang Asli school children in Temerloh, Pahang / Nurain Nabilah Roslan - Roslan, Nurain Nabilah (2015)
Microsporidia is an obligate intracellular, spore-forming fungus which has the polar tube used to infiltrate host cells like human and animals that may leads to microsporidiosis. There are 150 genera and 8 genera of microsporidia have been described infect human hosts. However, Enterocytozoon bieneusi, Encephalitozoon intestinalis, Encephalitozoon hellem and Encephalitozoon cuniculi are the most microsporidia species that causing gastrointestinal infection globally. Microsporidia can infect human through zoonotic, inter-human, water-borne, food-borne, transplacental and sexual transmission. Up to this date, many studies were focus more on immunocompromised patients with microsporidiosis compared than immunocompetent individuals. To the best of our knowledge, there is scanty data reported on microsporidiosis by using molecular methods in Malaysia. Therefore, this cross-sectional study was conducted from March to July 2015 in Sekolah Kebangsaan Penderas, Pahang to establish the existence of microsporidial infection among Orang Asli school children by determine the prevalence, species, risk factors and clinical manifestations of microsporidiosis. Eighty-nine stool samples were collected and examined for microsporidia spores using direct smear, formalin-ether sedimentation and modified formalin-ether sedimentation techniques. Then, all these slides were stained with modified Gram-chromotrope Kinyoun. The positive microscopic samples were further analyzed with polymerase chain reaction for identification of Enterocytozoon bieneusi. Pre-tested questionnaire was used in order to associate this infection with socio-demographic and clinical manifestations by using Pearson's Chi-square and univariate analysis tests. Overall, 69 (77.5%) stool samples showed positive with microsporidia microscopically. However, no significant difference was found between age groups (p = 0.090), genders (p = 0.824) and possible risk factors with intestinal microsporidiosis. Furthermore, there is no statistically significant between diarrhea (p = 0.226) and other gastrointestinal symptoms (p = 0.555) with microsporidia. None of E. bieneusi could be isolated from the microscopically positive samples in the present study. Since this study covered E. bieneusi species only, further studies to determine other microsporidia species need to be carried out in order to determine the species-specific prevalence of microsporidia among Orang Asli school children. Besides, different type of samples like water and animal samples should be examined in order to identify the right association socio-demographic and clinical manifestations with microsporidiosis.